2016
DOI: 10.1111/coep.12178
|View full text |Cite
|
Sign up to set email alerts
|

Output Growth and Structural Reform in Latin America: Have Business Cycles Changed?

Abstract: This paper documents important changes in real gross domestic product (GDP) growth of six large Latin American countries. The main results can be summarized as follows. First, there is evidence of a structural break in real GDP toward stronger mean growth and a substantial reduction in volatility. Second, the timing of the breaks suggests that the important changes in economic policies of the 1980s and 1990s have been effective in permanently improving economic growth in the region. These changes in the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…The authors found a size, time, and sign dependency of commodity prices on their country output. Similarly, Fossati [23] characterized the regime-specific behavior (two regimes) of the economic growth rates of Argentina, Brazil, Chile, Colombia, Mexico, and Peru, finding evidence of such a structural break. Miles and Vijverberg [24] tested the relationship between inflation and uncertainty in the UK and the U.S. and found, with their MS model estimation, that inflation targets and a proper budget lowered uncertainty in distress periods.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The authors found a size, time, and sign dependency of commodity prices on their country output. Similarly, Fossati [23] characterized the regime-specific behavior (two regimes) of the economic growth rates of Argentina, Brazil, Chile, Colombia, Mexico, and Peru, finding evidence of such a structural break. Miles and Vijverberg [24] tested the relationship between inflation and uncertainty in the UK and the U.S. and found, with their MS model estimation, that inflation targets and a proper budget lowered uncertainty in distress periods.…”
Section: Literature Reviewmentioning
confidence: 98%